Fostering an “investigating mindset”: Why is it important in digital forensic science education? - Horsman, Graeme; Ryser, Elenore; Shavers, Brett (Wiley, 2023)
The importance of the field of digital forensics (DF) is growing, where digital evidence is increasingly recognized as a crucial part of many investigations. As a result, criminal justice systems rely on DF practitioners to conduct robust investigations of digital devices and their data, and interpret and present these results in a way that can be relied upon. Undertaking this task appropriately requires a practitioner to have a range of skills; however, focus is often placed on the need for and importance of technical competency. Technical skills are vital in this role, that cannot be in dispute; however, this work discusses the need for practitioners to also have an “investigative mindset.”
Keywords: Digital forensics; Digital investigation; investigative mindset